Optimization and modeling of reactive conditions for free radical solution polymerization of SA-co-BA copolymer based on the yield using response surface methodology - Elarbe, Basem; Elganidi, Ibrahim; Norhayati, Abdullah; Kamal, Yusoh; Norida, Ridzuan (Penerbit UTM Press, 2021)
In the recent years, response surface methodology (RSM) is one of the most common optimization methods employed in the chemical process. The satisfactory model for predicting the maximum yield in solution polymerization has been a challenge due to various conditions during the synthesis process. In this study, interactive impacts of three parameters which are reaction time, concentration of initiator, and reaction temperature on the yield in free radical polymerization of SABA copolymer using toluene as solvent was investigated using experimental design central composite design (CCD) model under response surface methodology (RSM). The result showed the optimization conditions were reaction time of 7 h, initiator concentration of 1 wt %, and reaction temperature of 90 oC with the corresponding yield of 97.31%. The analysis of the regression model (ANOVA) detected an R2 value of 0.9844, that the model is able to clarify 98.44% of the data variation, and just 1.23% of the whole differences is not clarified by the model. Three experimental validation runs were carried out using the optimal replicate conditions and the highest average yield value obtained is 97.15%. There is an error of about 0.97% as compared to the expected value.Therefore, the results indicate that this model is reliable and is able to predict the yield response accurately. it established that the regression model is extremely significant, indicating a strong agreement between the expected and the experimental values of SABA yield.